TINJAUAN YURIDIS PERBUATAN MELAWAN HUKUM TERHADAP OBJEK SENGKETA TANAH PEKARANGAN DI DESA IKAN TUANBESI KABUPATEN MALAKA (STUDI KASUS PUTUSAN NOMOR 35/PDT.G/2023/PN ATB) - Tao, Fransiska; Mauritsius, Darius; Dinata, Husni Kusuma (Petitum Law Journal, 2025)
An unlawful act is any action that causes harm to another person, requiring the guilty perpetrator to compensate for the losses incurred. Acts against the law are regulated in Article 1365 of the Civil Code. In the land dispute case based on District Court Decision Number: 35/Pdt.G/2023/PN Atb, considering the lawsuit dated 31 July 2023 which was received and registered at the Registrar's Office of the Atambua District Court on 01 August 2023 where the Defendant committed an act of defiance without having valid evidence, Defendant I to Defendant III acted unlawfully and forcibly seized and controlled part of Maria Tay's land covering an area of ​​approximately 82 km. M2. This research aims to determine the arguments of the parties involved in Decision Number 35/Pdt.G/2023/PN Atb and the judge's considerations in Decision Number 35/Pdt.G/2023/PN Atb. The type of research used is normative research with the research materials used being primary and secondary legal materials. The legal material analysis method is carried out using descriptive and qualitative analysis. The results of this research are (1) The plaintiffs argued that they had rights to the land based on continuous possession, building a house, and paying taxes. On the other hand, the Defendant stated that based on the matrilineal system and customary law, the land belonged to them as a family inheritance, and they rejected the Plaintiff's claim which was deemed to have no clear legal basis. (2) Based on decision Number 35/PDT.G/2023/PN. Atb and the considerations presented by the Panel of Judges, the lawsuit submitted by the Plaintiff was declared inadmissible (Niet Ontvankelijke Verklaard) because there was ambiguity in the lawsuit, both in terms of subject, object and the arguments put forward. This lawsuit contains uncertainties that cause doubts in the evidence, especially regarding land ownership status, land area, and the boundaries of the land in dispute.